Pengaruh Budaya Organisasi Dan Kompensasi Terhadap Kinerja Pegawai PT. Pegadaian Kanwil XII Surabaya Yang Dimediasi Oleh Komitmen Organisasi - Astrid Maulidina Wibiarisky; Suci Rina Sari; Bangun Wisnumaya; Chamariyah Chamariyah (Universitas 45 Surabaya, 2025)
The effect of organizational culture and compensation on employee performance at PT Pegadaian Kanwil XII Surabaya which is mediated by organizational commitment. This type of research is explanatory, namely to test the hypothesis between the hypothesized variables to be tested. using a quantitative approach, the research sample was 57 respondents. In this study, the data will be processed using SEM-PLS data analysis. The objectives of this study are: 1) To test and analyze whether organizational culture has a significant effect on employee performance. 2) To test and analyze whether organizational culture has a significant effect on organizational commitment. 3) To test and analyze whether compensation has a significant effect on employee performance. 4) To test and analyze whether compensation has a significant effect on organizational commitment. 5) To test and analyze whether organizational commitment has a significant effect on employee performance. 6) To test and analyze whether organizational culture has an indirect effect on employee performance mediated by organizational commitment. 7) To test and analyze whether compensation has an indirect effect on employee performance mediated by organizational commitment. The results showed that: 1) Organizational culture has a positive and significant effect on employee performance. This is evidenced by the original sample value of 0.286 and the p-values of 0.007. 2) Organizational culture has a positive and significant effect on organizational commitment. This is evidenced by the original sample value of 0.501 and p-values of 0.000. 3) Compensation has a positive and significant effect on employee performance. This is evidenced by the original sample value of 0.252 and p-values of 0.016. 4) Compensation has a positive and significant effect on organizational commitment. This is evidenced by the original sample value of 0.380 and p-values of 0.000.5) Organizational commitment has a positive and significant effect on employee performance. This is evidenced by the original sample value of 0.429 and p-values of 0.000. 6) Organizational culture has a significant positive effect on employee performance mediated by organizational commitment. This is evidenced by the original sample value of 0.163 and p-values of 0.001. 7) Compensation has a significant positive effect on employee performance mediated by organizational commitment. This is evidenced by the original sample value of 0.215 and p-values of 0.002.